A study of problems of lecturers in using ICT applications in online teaching at Souphanouvong University during the COVID-19 pandemic: https://doi.org/10.69692/sujournal2022.8.2.31-38 - SISOMBATH, Sithonh; PHAIYAVONG, Somchay; THIPPHAPHONE, Kinnaly; PHATHOUMVAN, Phanthamanut; NORDALA, Phouvong (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This article aimed to present research result at Souphanouvong University in 2021. The objectives were to find out the applications used by lecturers for teaching online and to determine the problems of lecturers in using ICT applications to teach online. This research used a quantitative method. The researchers contacted the 340 lecturers who were working on campus at Souphanouvong University in the academic year 2020-2021. However, only the respondents who taught online during the pandemic were included for compiling the results. Thus, the population consisted of 99 lecturers (29.11%). The research instrument was an online questionnaire through Google Forms with 16 closed and open-ended questions. The SPSS program version 20 was used to calculate all the data. Analysis of data on the type of ICT applications applied by the lecturers showed that 76.0% applied WhatsApp, 71.0% applied Zoom, 51.5 % applied Facebook Groups, 29.3% applied Google Classroom and Google Meet, and only 6.0% applied YouTube videos. Results on the types of problems experienced by lecturers were as follows: 97.0% of the respondents pointed out that the internet was slow; 50.5% said that their computers were not working properly or some had no computers; 49.5% said that they had difficulties with online assessment; 44.4% said they had a trouble with recording videos of their teaching and creating an online classroom; and 41.4% said that they were confused with using applications to teach online.